A SITUATIONAL ANALYSIS OF CHINA ROLE IN AFGHAN PEACE PROCESS - Samiullah; Mazhar Islam; Sanaullah; Shakeel Iqbal; Rafeed Ullah Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The people of Afghanistan have been suffering for the last two decades and the presence of American forces in Kabul has not helped accomplish any constructive political outcomes up until now. A hasty withdrawal of US troops from Afghanistan will not be a mature step towards political stability in Afghanistan. The Chinese leadership is exploring all possible measures to establish lasting peace in Afghanistan. The aim of this study is to find out why China played an active role in the Doha deal. The study is qualitative in nature, using an exploratory method. Beijing not only played a vital role in paving the ground for the Afghan reconciliation process, but also helped the current unity regime in Kabul to improve law and order. A stable Afghanistan would be an oasis in the heart of Central Asia, and if Afghanistan is unstable, it will be a safe haven for most religious extremists and terrorists. It will also be a security threat to the entire regional countries around Afghanistan. Beijing has been doing its best to end the long bloodshed in Afghanistan.